2003
DOI: 10.1099/jmm.0.04973-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of Candida strains isolated from women with vaginal candidiasis in Malaysia

Abstract: The aims of this study were to compare the genetic relatedness of: (i) sequential and single isolates of Candida strains from women with recurrent vaginal candidiasis (RVC); and (ii) Candida strains from women who had only one episode of infection within a 1-year period. In total, 87 isolates from 71 patients were cultured, speciated and genotyped by random amplification of polymorphic DNA (RAPD) analysis. Patients were categorized into three groups, namely those with: (i) a history of RVC from whom two or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 19 publications
7
49
2
2
Order By: Relevance
“…These different Candida species have been associated with differences in the morphotype and virulence factors such as germ tube and mycelia formation, proteinase secretion, the changes in vaginal pH, phenotypic switching and ability to cause vaginal candidiasis (Sobel et al, 1981;Sobel, 1985;Hunter et al, 1989;Cutler, 1991;De Bernardis, et al, 1993;Cassone et al, 1995;Hube, 1996;Samaranayake et al, 2003;. However, a significant increase in non-albicans Candida species and formation of virulence factors have been reported to be associated with recurrent Candida vaginitis (Sobel, 1992;Sobel, 1998;Chong, et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These different Candida species have been associated with differences in the morphotype and virulence factors such as germ tube and mycelia formation, proteinase secretion, the changes in vaginal pH, phenotypic switching and ability to cause vaginal candidiasis (Sobel et al, 1981;Sobel, 1985;Hunter et al, 1989;Cutler, 1991;De Bernardis, et al, 1993;Cassone et al, 1995;Hube, 1996;Samaranayake et al, 2003;. However, a significant increase in non-albicans Candida species and formation of virulence factors have been reported to be associated with recurrent Candida vaginitis (Sobel, 1992;Sobel, 1998;Chong, et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
“…The most common vaginal isolate include C. albicans with a prevalence of 70-90% and less frequently non-albicans Candida species such as C. tropicalis, C. glabrata (Torulopsis glabrata), C. kefyr (C. pseudotropicalis), C. krusei, C. famata, C. parapsilosis, and C. lusitaniae (Xu et al, 1999;Abu-Elteen, 2001;Chong et al, 2003;. These different Candida species have been associated with differences in the morphotype and virulence factors such as germ tube and mycelia formation, proteinase secretion, the changes in vaginal pH, phenotypic switching and ability to cause vaginal candidiasis (Sobel et al, 1981;Sobel, 1985;Hunter et al, 1989;Cutler, 1991;De Bernardis, et al, 1993;Cassone et al, 1995;Hube, 1996;Samaranayake et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes of this yeast have been associated with different infection sites (18) and with susceptibility to antifungal drugs (20). Recently, Chong et al (4), in a study of genetic similarities by random amplification of the polymorphic DNA (RAPD) of Malaysian patients with VVC and RVVC, found that patients with RVVC are more frequently colonised by the same isolate of Candida. However, little is known about the relation of the genotypes with the virulence capacity of C. albicans in the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…About 20 to 25% of healthy and completely asymptomatic women present positive vaginal secretion cultures for this fungus. Around 75% of adult women have at least one episode of vulvovaginal candidiasis (VVC) during their life, with prevalence of C. albicans in 70-90% (4). Some of these patients will experience episodes again and 5% will suffer recurrent VVC (RVVC) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Chong et al [90] in their study in Malaysia showed that C. albicans that cause RVVC are less similar to each other than the strains causing sporadic VVC, thus suggesting that the former may represent more virulent sub-types [90]. Soll et al [91] reported that although the genotype remains the same there is phenotype switching of C. albicans in RVVC [91] and Schroppel et al [92] observed yeast genetic instability with repeated courses of antifungal treatments [92].…”
Section: Microbial Factorsmentioning
confidence: 99%